AN ANALYSIS OF POLITENESS STRATEGIES USED BY TWO SPEAKERS ON INTERNATIONAL LANGUAGE EDUCATION CONFERENCE - Salsabila, Zahra Muthia; Yugafiati, Rasi; Anggraeni, Anita (IKIP Siliwangi, 2024)
Politeness strategies is a branch of pragmatic. When people interact and communicate, they should know how to respond to the answer or topic to lead a pleasant conversation with the right strategy. The purpose of this study is to examine how two presenters on an international webinar employed four different sorts of politeness strategies: off-record politeness, bald-on-record, positive politeness and negative politeness. The researcher also intends to examine the dominant strategy employed there. In this study, the qualitative descriptive method was used. The information was obtained via recording of an international webinar. The data was analyzed using Brown and Levinson's (1987) theoretical framework. Following analysis, the findings showed that both speakers only employed the three politeness methods of negative politeness, positive politeness and off-record politeness. Both speakers do not employ